Pengaruh Faktor Pengetahuan dan Aksesibilitas Dalam Pemanfaatan Kelambu Insektisida - Mariana Isir; Alva Cherry Mustamu; Adriana Egam (Jurnal Ilmiah Kesehatan Sandi Husada, 2021)
Introduction; Malaria suffers quite a lot and is still a public health problem because of its high morbidity and mortality rates. This infectious disease can cause death, especially in high-risk groups, namely infants, toddlers, and pregnant women. One of the groups that are vulnerable to malaria in pregnant women. Aim; This study aims to determine the knowledge, accessibility, and use of insecticide bed nets during pregnancy. Method; This type of research is descriptive-analytical. With a cross-sectional approach with a sample of 78 pregnant women by means of accidental sampling. Data analysis was performed using a frequency test. Result; That 57.69% of respondents about insecticide bed nets from mass media such as the internet, newspapers, social media. as many as 65.38% of respondents had at least 1 insecticide bed net in their house obtained from the puskesmas (55.13%). as much as 34.62% of respondents said that insecticide-treated bed nets were given to them at the 3rd trimester of pregnancy. However, 35.9% have not used it properly. Respondents hoped that insecticide bed nets should be provided free of charge (43.59%). Conclusion; All pregnant women are ready to use insecticide bed nets if adequate information and bed nets are available at affordable prices or provided free of charge